Managing coastal heritage in the Westfjords : case study of 19th century Norwegian whaling stations - Tyas, Alexandra, 1992- (2016)
Verkefnið er unnið við Háskólasetur Vestfjarða Verkefnið er lokað til 31.01.2019. Coastal cultural heritage sites have received a lot of attention in recent years due to the threats they face, both anthropogenic and natural. The surveying of sites at risk is therefore prioritised, in order to record sites before they are lost to the sea. However, in countries where the management structure is lacking, this prioritisation does not occur. It is therefore unknown how many sites are at risk, from what threats, and if sites have already been lost. This thesis set out to explore the state of heritage management in Iceland, with a focus on coastal and underwater sites. In order to address this, case studies of four 19th century Norwegian whaling stations in the Westfjords were chosen for archaeological surveying, as representatives for both coastal and underwater heritage sites. A background analysis on the current Icelandic management structure, legal environment, and current threats to coastal heritage sites was completed. The conclusions suggest that the legal environment in Iceland is sufficient; however it is the implementation and enforcement of the laws which is lacking. Underlying issues seem to be the problem of funding for archaeology, and the lack of value of the sites to the local communities. The future preservation and protection of coastal heritage sites therefore depends largely on public engagement, education, and increased awareness of the social and economic benefits coastal heritage sites can provide. Síðustu ár hafa menningarminjar við strendur landsins fengið talsverða athygli vegna þeirra mannlegu- og nátturulegu þátta, sem ógna menningarminjum við sjávarsíðuna. Það er forgangsatriði að rannsaka slík svæði og mikilvægt er að fornleifaskrá þau áður en þau verða eyðileggingu að bráð. Í löndum þar sem eftirlit á slíkum svæðum er lítið sem ekkert, er forgangsröðun í minjavörslu ekki til staðar, því er það ómöglegt að geta sér til um hversu mörg svæði eru í hættu, vegna hvaða orsaka og hvort ...